An improved distributed video coding with low-complexity motion estimation at encoder - Yang, Hsin-Ping; Hsieh, Hsiao-Chi; Chang, Sheng-Hsiang; Chen, Sao-Jie (Proceedings / IEEE International SOC Conference, 2015)
Distributed Video Coding (DVC) is a novel scheme which is different from the state-of-the-art video compression standards. A specific characteristic of DVC is its use of a low complexity encoder. However, there exists an issue on the DVC, which requires redundant decoding time. Therefore, low-complexity motion estimation algorithm and skip mode have been applied to the encoder of a hybrid DVC to reduce half of the decoding time. The computational complexity of the encoder only increases slightly with respect to the hybrid DVC, which is still far less than H.264/AVC no motion. In some cases, the encoding time is even reduced instead of being increased. Besides, the rate-distortion performance is improved in high motion videos. However, the rate-distortion performance does not decrease in the static video, because of the added motion estimation.